PsycEXTRA Dataset 1999
DOI: 10.1037/e304702004-001
|View full text |Cite
|
Sign up to set email alerts
|

Families and Schools Together: Building Relationships.

Abstract: This bulletin profiles a program, Families and Schools Together (FAST), that brings at-risk children and their families together in multifamily groups to strengthen families and increase the likelihood that children will succeed at home, at school, and in the community. Drawing on research and family therapy, FAST builds protective factors for children and increases parent involvement with the family, other parents, the school, and the community. Families participate in an initial 8-week program, followed by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Rather than implementing new programs, existing programs that had shown promise at either local, for example, On-Campus Intervention Program (OCIP;Family Resources, 2002), or national levels, for example, Families and Schools Together (FAST;McDonald, 1989;McDonald & Frey, 1998) were designated to expand availability and fill in gaps for services offered to children and families. To determine expansion, risk factors were mapped across the school district and compared with current services and programs offered by both the school system and other providers in the community, and major gaps identified within the geographical areas.…”
Section: Overview Of the Project Mission Plans And Proceduresmentioning
confidence: 99%
“…Rather than implementing new programs, existing programs that had shown promise at either local, for example, On-Campus Intervention Program (OCIP;Family Resources, 2002), or national levels, for example, Families and Schools Together (FAST;McDonald, 1989;McDonald & Frey, 1998) were designated to expand availability and fill in gaps for services offered to children and families. To determine expansion, risk factors were mapped across the school district and compared with current services and programs offered by both the school system and other providers in the community, and major gaps identified within the geographical areas.…”
Section: Overview Of the Project Mission Plans And Proceduresmentioning
confidence: 99%
“…The intervention we test, which stimulates social capital, is Families and Schools Together (FAST), a program designed to develop relations of trust and shared expectations among parents, school staff, and children (McDonald 2002; McDonald and Frey 1999). FAST has been identified as an exemplary evidence-based model by the U.S. Department of Education and the Office of Juvenile Justice and Delinquency Prevention, and it is listed in the National Registry of Effective Prevention Programs of the U.S. Substance Abuse and Mental Health Services Administration (Office of Juvenile Justice and Delinquency Prevention 2006; US Department of Education Office of Educational Research and Improvement 1998).…”
Section: Methodsmentioning
confidence: 99%
“… 1 Descriptions of FAST sessions are laid out in materials such as McDonald and Frey (1999) and McDonald (2002); they were verified by on-site observations during this study. …”
mentioning
confidence: 94%
“…The program was originally designed to increase social capital among minority families, and it demonstrated that the active engagement of parents in the program led to improved behavioral and academic outcomes of their children. The program was implemented in 47 states and 16 countries (McDonald & Frey 1999;McDonald 2002).…”
Section: Datamentioning
confidence: 99%
“…Consider an intervention that is administered at the school level but where the variables of interest are measured at the within-school (child, parent) level. In the example that will serve as the case study for this article, interest centers on a randomized intervention referred to as Families and Schools Together (FAST; L. McDonald & Frey, 1999;McDonald, 2002). The FAST intervention is designed to increase parent-parent and parentschool social capital among low-income families.…”
Section: Introductionmentioning
confidence: 99%